Research progress on damage-associated molecular patterns in acute kidney injury - Li, Jiajia; Hu, Zhangxue (Frontiers in Immunology, 2025)
Acute kidney injury (AKI) is a clinical syndrome characterized by a sudden dysfunction of the kidney, which is common worldwide, with a relatively high incidence and mortality rate. Damage to the proximal renal tubule is a pathological hallmark of AKI, and inflammation triggered by the overactivation of the immune system is a common cause of proximal renal tubular injury, which is an important contributing factor in AKI exacerbation. Damage-associated molecular patterns (DAMPs) are endogenous molecules released by cells in response to external stimuli that can trigger an inflammatory response by binding to specific pattern recognition receptors (PRRs). Numerous studies have indicated that when the kidney is exposed to external stress or chemical stimuli, injured cells actively secrete or passively release various DAMPs, which can exacerbate or attenuate kidney injury by stimulating or inhibiting the inflammatory response through binding to the appropriate receptor. Currently, there is a lack of early diagnostic biomarkers and specific therapeutic strategies for AKI in the clinic have been established, and given the important role of the release of DAMPs in the regulation of inflammatory response, they will highly likely become favorable candidate biomarkers and clinical therapeutic targets for AKI. Therefore, a deeper understanding of the types of DAMPs and the specific mechanisms of their actions will provide more possibilities for the specific AKI diagnosis and treatment.